Screening for tuberculosis in family and household contacts in a rural area in Ethiopia over a 20-month period - Jose Manuel Ramos; Dejere Biru; Abraham Tesfamariam; Francisco Reyes; Miguel Górgolas (International Journal of Mycobacteriology, 2013)
The purpose of this study is to describe the experience of the completion of the Tuberculosis (TB) Contact Screening Logbook (TB-CSL). The TB-CSL was retrospectively analyzed from July 2007 until June 2012. During the study period, 122 patients were included in the TB-CSL; however, 17 (13.9%) patients with TB were written in the TB-CSL, but without registering any contacts. Of the 105 TB patients with contacts registered, the family and household contacts were finally performed in 68 index TB patients (55.7% of TB patients). These 68 index TB cases had 299 family and household contacts; the median contact per patient was 4.4 ( ±1.9). Of the 299 contacts, 160 (53.5%) were screened. The median of those screened per patient was 2.3 ( ±1.9). Of the 160 family and household contacts screened, 34 (31.3%) of them were children ≤5 years of age. TB was diagnosed after screening in 16 (10.1%) contacts. Isoniazid preventive therapy was prescribed in 22 of 34 (64%) children <5 years of age. Alternative methods should be implemented in rural areas to improve TB screening contacts, especially in children under 5 years of age.